Investigation of architectural elements of the Davao City jail with respect to rehabilitative treatment - Sy, Mary Grace T. (2005)
Architectural design of a correctional facility must aid its operational policies and philosophies. Since the Bureau of Jail Management and Penalogy (BJMP) of the Philippines seeks to safely confine and rehabilitate offenders, physical components of a jail in the country should reflect its goals and objectives. The purpose of the study is to investigate existing architectural elements that efficiently facilitate the programs and services of the Davao City Jail and conceptualize a jail environment that is conducive for rehabilitation of inmates. The dissertation is a study specifically of the Davao City Jail. The study investigated the quality of living spaces, facilities for the basic services, spaces for educational and religious programs, and the sense of security and control in all areas if such are effective in delivering the said purpose of a Philippine Correctional System. Data of the study include the ocular survey of the facilities. A questionnaire was administered to a sample of inmates to elicit their response to physical setup and services offered by the Davao City Jail. Interviews with the inmates were also conducted to verify the results of the survey. The jail officers were interviewed as well as to provide familiarization of jail management and administration. The results should determine the spaces and facilities that should be retained and those that need to be improved and also what kind of improvement is needed. From findings, programmatic and architectural recommendations were generated.